Concepts and Forms of Realization of Citizens’ Voting Rights in Local Elections - Anton Voitenko (Юридичний часопис Національної академії внутрішніх справ, 2021)
The purpose of the publication is to study the concept and forms of realization of voting rights of citizens in local elections in Ukraine, in order to understand the legal category and further improve the electoral legislation of Ukraine. Methodology. During the research of the scientific article the general and special-legal methods were used: system analysis, comparative-legal, dialectical approach, system-structural, applied methods of scientific knowledge, which provides the purpose and objectives of scientific research. Scientific novelty. The novelty of the study lies in a comprehensive analysis of the concept and forms of realization of voting rights of citizens in local elections. The article examines the concept of realization of voting rights of citizens in local elections, taking into account theoretical scientific approaches to understanding the implementation of the right. Based on the analysis of the Laws of Ukraine, which regulate the issue of citizens 'suffrage in local elections, it is determined that the exercise of citizens' suffrage is the most influential form of democracy in the country. The study proved that it is the legal forms of exercising the voting rights of citizens in local elections that have practical consequences, which in turn are the realization of the will of the people and are universally binding on public authorities. It is noted that the residency requirement is one of the most serious obstacles to the exercise of citizens' voting rights in local elections. Conclusions. The realization of the voting rights of citizens in local elections is a process during which the subject of suffrage, aware of their actions (inaction), guided by regulations, enters into legal relations, which are the legal expression of political relations. The legislative requirement for a person to belong to a certain territorial community as a condition for exercising the right to vote in local elections is the biggest obstacle to exercising their right to vote. The main forms of exercising the right to vote by citizens in local elections are: implementation, use and observance, through which direct suffrage is exercised